2015
DOI: 10.1097/ccm.0000000000001082
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomous “Good Outcome” Indicates Mobility More Than Cognitive or Social Quality of Life

Abstract: Objective Worthwhile interventions for intracerebral hemorrhage (ICH) or subarachnoid hemorrhage (SAH) generally hinge on whether they improve the odds of “good outcome.” While good outcome is correlated with mobility, correlations with other domains of health-related quality of life (HRQoL), such as cognitive function (CF) and social functioning, are not well described. We tested the hypothesis that good outcome is more closely associated with mobility than other domains. Design We defined “good outcome” as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Recent small studies have shown that they correlate well with the mRS but have greater capacity to discriminate smaller but still meaningful change. 23,24 In order to address the issue of futility, future research efforts should use pooled analysis of data from recent trials as well as large imaging based observational studies that enroll either patients without the TRAITs or all comers with a subsequent analysis of outcome by imaging profile to derive futility thresholds for current reperfusion therapy. 25 …”
Section: Opportunities For Standardizationmentioning
confidence: 99%
“…Recent small studies have shown that they correlate well with the mRS but have greater capacity to discriminate smaller but still meaningful change. 23,24 In order to address the issue of futility, future research efforts should use pooled analysis of data from recent trials as well as large imaging based observational studies that enroll either patients without the TRAITs or all comers with a subsequent analysis of outcome by imaging profile to derive futility thresholds for current reperfusion therapy. 25 …”
Section: Opportunities For Standardizationmentioning
confidence: 99%
“…While we found that all patients who had delirium with agitation had some level ofmotor disability, HRQoL provides additional insights to outcomes that might be missed by a summary scale. (34)…”
Section: Resultsmentioning
confidence: 99%
“…Adverse events associated with phenytoin are relatively easy to detect. 4 Levetiracetam has fewer side effects than phenytoin, and any adverse effects on cognition or behavior are likely to be detected only in patients already considered to have a “good outcome.” 13 Other validated scores of health-related quality of life and cognition could be a useful adjunct. 14, 15 …”
Section: Discussionmentioning
confidence: 99%